The value of the plate mechanical properties in a case of thoracoplasty at the congenital pectus excavatum - Dihtiar, Valerii; Kaminska, Marianna; Karpinsky, Mykhaylo; Karpinska, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
Surgical treatment of a congenital pectus excavatum (CPE) includes using of a plate that holds the correct anatomical shape of the chest for a long time. Before implanting the plate behind a sternum, it is bent so that after correcting the deformation, it reproduces shape of the ribs on both sides and fits close to them. Displacement and rotation are the most frequent complications after plate implantation. Therefore, mechanical properties of the plate, such as: strength, ability to withstand the load during surgery and in the long term period — is one of the main guarantees to obtain the good result. Objective. To study the mechanical properties of the plate which is used for thoracoplasty at CPE under conditions comparable to real loads in order to gain maximal correction. Methods. Experimental bending tests were performed on 5 standard plates of 2.5 mm thick, 13 mm width and 200 mm length, made from titanium Ti6–AL4–V (according to ISO 5832-3). All plates were bent with a special surgical instrument according to the anatomical shape of a chest, using method of surgery by D. Nuss. All plates supports were placed on a distance from the fixing screws. The force of bending load was applied to the middle of the plate, gradually increasing from 150 to 600 H with a step 50 H. At each value of the loading we measured the height of the plate edge elevation. Results. Under load conditions of 600 H, the elevation of a plate edge did not exceed 3 mm and was equal to (2700 ± 177) μcm. In a case of twice lower loads (300 H), value of lifting edge of the plate decreased in three times and was (700 ± 85) μcm. Changes that happened under loading were the same for all five types of the plate. Conclusions. It is proved that the plates can fully withstand corrective loads with a minimal deformation after thoracoplasty. The discrepancy between the plate shape in the lateral parts to the restored thorax is caused by the changing of configuration of the last one and increasing in the anteroposterior size. Key words. Plate, mechanical properties, thoracoplasty.